2014
DOI: 10.18632/oncotarget.2796
|View full text |Cite
|
Sign up to set email alerts
|

CD117+ cells in the circulation are predictive of advanced prostate cancer

Abstract: Circulating tumor cells (CTCs) are associated with cancer progression, aggressiveness and metastasis. However, the frequency and predictive value of CTCs in patients remains unknown. If circulating cells are involved in tumor aggressiveness and metastasis, then cell levels should decline upon tumor removal in localized cancer patients, but remain high in metastatic patients. Accordingly, proposed biomarkers CD117/c-kit, CD133, CXCR4/CD184, and CD34-positive cell percentages in the blood of patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…In addition to CXCL12, stem cell factor (SCF), another osteoblast-derived factor that regulates HSC function [47], may promote prostate cancer bone metastasis. Indeed, circulating tumor cells [48] and bone metastatic samples [49] obtained from prostate cancer patients express a receptor for SCF, c-Kit or CD117, which is highly expressed in advanced prostate cancer. The effects of cabozantinib (XL184), a small molecule inhibitor which targets c-Kit, were evaluated in a phase II randomized discontinuation trial in men with castration-resistant bone metastatic prostate cancer [50].…”
Section: Mechanisms Of Prostate Cancer Bone Metastasismentioning
confidence: 99%
“…In addition to CXCL12, stem cell factor (SCF), another osteoblast-derived factor that regulates HSC function [47], may promote prostate cancer bone metastasis. Indeed, circulating tumor cells [48] and bone metastatic samples [49] obtained from prostate cancer patients express a receptor for SCF, c-Kit or CD117, which is highly expressed in advanced prostate cancer. The effects of cabozantinib (XL184), a small molecule inhibitor which targets c-Kit, were evaluated in a phase II randomized discontinuation trial in men with castration-resistant bone metastatic prostate cancer [50].…”
Section: Mechanisms Of Prostate Cancer Bone Metastasismentioning
confidence: 99%
“…The FACS analysis has assessed not only the mesenchymal origin but also the non-malignancy of our clone. In particular, the negative results obtained analyzing the main surface markers expressed within the majority of solid tumors (CD133, CD117, CD34 and CD271) (23)(24)(25)(26)(27), together with the cell inability to form colonies in soft agar (28), confirmed that no malignant transformation occurred during cloning of PDL cells. In order to assess its potential and capability to differentiate into different lineages, we induced the clonal CD44+ PDL line toward adipogenic and osteogenic phenotypes.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, inhomogeneous use of hormones in this study could confound the findings. Of note, some molecular markers such as CD117+ cell levels and miRNAs (miR-103, 125b, and 222) expression have been proposed for the prediction of biochemical failure for patients after RP and decide timing of salvage treatment [32, 33]. The prospective multi-center study will be needed to confirm the results.…”
Section: Discussionmentioning
confidence: 99%